2001
DOI: 10.1210/endo.142.1.7895
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Two Forms of Gonadotropin-Releasing Hormone Messenger Ribonucleic Acid in Human Granulosa-Luteal Cells**This work was supported by grants from the Medical Research Council of Canada.

Abstract: Until recently, the primate brain was thought to contain only one form of GnRH known as mammalian GnRH (GnRH-I). The recent cloning of a second form of GnRH (GnRH-II) with characteristics of chicken GnRH-II in the primate brain has prompted a reevaluation of the role of GnRH in reproductive functions. In the present study, we investigated the hormonal regulation of GnRH-II messenger RNA (mRNA) and its functional role in the human granulosa-luteal cells (hGLCs), and we provided novel evidence for differential h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The classical mammalian GnRH (now referred to as GnRH-I) as well as a second form of GnRH (GnRH-II) that is identical to chicken GnRH-II are expressed in humans [5,6]. In addition to the well-established function of GnRH in the control of gonadotropin secretion from the pituitary, both GnRH-I and GnRH-II have been shown to exert autocrine and/or paracrine effects in extrapituitary tissues, including the ovary [7,8]. GnRH-I and its receptor are expressed in 80% of human ovarian epithelial tumors, ovarian surface epithelial (OSE) cells, and ovarian cancer cell lines [9,10], suggesting that this decapeptide hormone may be an autocrine and/or paracrine regulator of the OSE and play a role in the pathophysiology of ovarian cancer [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The classical mammalian GnRH (now referred to as GnRH-I) as well as a second form of GnRH (GnRH-II) that is identical to chicken GnRH-II are expressed in humans [5,6]. In addition to the well-established function of GnRH in the control of gonadotropin secretion from the pituitary, both GnRH-I and GnRH-II have been shown to exert autocrine and/or paracrine effects in extrapituitary tissues, including the ovary [7,8]. GnRH-I and its receptor are expressed in 80% of human ovarian epithelial tumors, ovarian surface epithelial (OSE) cells, and ovarian cancer cell lines [9,10], suggesting that this decapeptide hormone may be an autocrine and/or paracrine regulator of the OSE and play a role in the pathophysiology of ovarian cancer [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular signaling differences have been reported between the cognate receptors for GnRH‐I and GnRH‐II. Consistent with GnRHR1, GnRHR2 couples to G αq/11 to initiate inositol triphosphate production, mobilization of calcium and protein kinase C (PKC) activation (Kang et al, 2001; Liu et al, 2009; Millar, 2003). Although limited studies exist, signaling pathways downstream of PKC differ following ligand binding to either GnRHR‐I and GnRHR‐II.…”
Section: Gnrhr‐iimentioning
confidence: 99%
“…GnRH‐II and its receptor are present in many cells and tissues of the female reproductive tract (Millar, 2003); however, very little research has been performed to elucidate how this ligand‐receptor interaction mediates female reproductive processes. Although data is limited, GnRH‐II and/or GnRHR‐II have been implicated in ovarian steroidogenesis, including the regulation of progesterone synthesis in humans (Kang et al, 2001), rhesus macaques (Siler‐Khodr et al, 2004, 2006) and baboons (Siler‐Khodr et al, 2003). Therefore, we sought to examine the effect of GnRHR‐II KD on progesterone production in gilts.…”
Section: Role Of Gnrh‐ii and Gnrhr‐ii In The Female Pigmentioning
confidence: 99%
“…Molecular analysis has shown that the human type-2 GnRH receptor contains a stop codon and is thought to be inactive (Faurholm et al 2001;Neill 2002). This is odd in light of the wide distribution of GnRH II mRNA in many human tissues including the brain, prostate, ovary, kidney, and bone marrow (White et al 1998;Choi et al 2001;Kang et al 2001). The high affinity of GnRH II for the type-1 GnRH receptor suggests that, despite the type-2 GnRH receptor in humans being nonfunctional, GnRH II could act through the type-1 GnRH receptor (Millar 2003).…”
Section: Gnrh II and The Type-2 Receptormentioning
confidence: 99%